Telomere length and outcome of treatment for pulmonary tuberculosis in a gold mining community - Katoto, Patrick D. M. C.; Kayembe-Kitenge, Tony; Pollitt, Krystal J. Godri; Martens, Dries S.; Ghosh, Manosij; Nachega, Jean B.; Nemery, Benoit; Nawrot, Tim S. (Scientific reports, 2021)
Telomere length (TL) is a marker of ageing and mitochondrial DNA (mtDNA) is an early marker of inflammation caused by oxidative stress. We determined TL and mtDNA content among active pulmonary tuberculosis (PTB) patients to assess if these cellular biomarkers differed between artisanal miners and non-miners, and to assess if they were predictive of treatment outcome. We conducted a prospective cohort study from August 2018 to May 2019 involving newly diagnosed PTB patients at three outpatient TB clinics in a rural Democratic Republic of Congo. We measured relative TL and mtDNA content in peripheral blood leukocytes (at inclusion) via qPCR and assessed their association with PTB treatment outcome. We included 129 patients (85 miners and 44 non-miners) with PTB (median age 40 years; range 5–71 years, 22% HIV-coinfected). For each increase in year and HIV-coinfection, TL shortened by − 0.85% (− 0.19 to − 0.52) (p ≤ 0.0001) and − 14% (− 28.22 to − 1.79) (p = 0.02) respectively. Independent of these covariates, patients with longer TL were more likely to have successful TB treatment [adjusted hazard ratio; 95% CI 1.27 for a doubling of leucocyte telomere length at baseline; 1.05–1.44] than patients with a shorter TL. Blood mtDNA content was not predictive for PTB outcome. For a given chronological age, PTB patients with longer telomeres at time of diagnosis were more likely to have successful PTB treatment outcome.